Cooperative Spectrum Sensing Based on Dempter-Shafer Theory of Evidence in Cognitive Radio Network - Shujing Xie; Lianfeng Shen (Dianxin kexue)
Cognitive radio has the advantage of high spectrum utilization since the spectrum can be shared by primary and secondary user.Meanwhile,the new adaptable characteristic is required for the secondary user.On the basis of analyzing D-S theory of evidence,a novel distributed cooperative spectrum sensing scheme was presented,which modified the combination equation for conflicting evidence source,and the BPA function based on fuzzy degree calculation was redefined.Simulation results show that the proposed scheme can sense the available spectrum in the cognitive radio networks very well,and can be used as a general spectrum sensing scheme in AWGN and Rayleigh fading channel when compared with the traditional ＂and＂,＂or＂ fusion rules and other D-S theory of evidence schemes in the previous literature.